Jigsaw Type Cooperative Learning Model to Improve Learning Outcomes of Natural Science (Study at SD Negeri 2 Bokori) - Iskandar, Iskandar (International Journal of Management and Education in Human Development, 2021)
This research was motivated by the low scores of science subjects at SD Negeri 2 Bokori which were caused by the science learning process that had been carried out so far, which always applied traditional learning patterns. This type of research is classroom action research, as a research procedure that produces descriptive data in the form of written or spoken words from observable evaluation results. The population of this study were 28 students of Class VI SD Negeri 2 Bokori. The results obtained indicated that the application of the jigsaw cooperative learning model can improve the learning outcomes of Class VI students at SD Negeri 2 Bokori for science subjects, the achievement of performance indicators has been achieved where the classical average in cycle I reaches 73.23 and the percentage of classical completeness 77.93, while in cycle II it has increased where the classical average has reached 78.57 and the percentage of completeness in classical has reached 82.14. Based on this, the performance indicator in this study is the classical average of 75 and the classical success percentage is 80%.